Competitiveness of Ciit Sahiwal - Sabir, Raja Irfan; Shahnawaz, Muhammad; Mian, Bilal Iqbal; Bahadur, Waseem; Zulfiqar, Salman (International Journal of Management and Sustainability, 2013)
This research aims to evaluate the competitiveness of Comsats Institute of Information Technology (CIIT) Sahiwal with Other Higher Educational Institutions (OEI) of Sahiwal. An Early Warning System (EWS) has been used to analyze expectations and actual feelings of respondents from CIIT and OEI of Sahiwal. The research findings reveal that: (a) CIIT Sahiwal has more innovative capabilities and more competitive advantage as compared to OEI of Sahiwal. (b) The students of CIIT Sahiwal are almost satisfied from their institution however there is a need for further improvement especially regarding social responsibility. (c) The students of OEI of Sahiwal are completely unsatisfied on some points like human resources (HR), government support (GS), innovative learning (IL), library (LB) and social responsibility (SR) and showed almost satisfaction on some other points like research work (RW), international cooperation (IC), examination and assessment (EA) and fee structure (FS).